Colloids for nano- and biotechnology - Hórvölgyi, Zoltán (Springer-Verlag Berlin Heidelberg, 2017)
This volume contains a selection of the papers presented at the 9th Conference on Colloid Chemistry. A colloid chemical approach to nano- and biotechnology was one of the main topics of the meeting held in Siófok, Hungary in October 2007. It was organized by the Hungarian Chemical Society in cooperation with leading Hungarian universities and the Hungarian Academy of Sciences.